Cognition and affect in consumer decision making: Conceptualization and validation of added constructs in modified instrument - Shakeel Ahmad Sofi; Faizan Ashraf Mir; Mubashir Majid Baba (Future Business Journal, 2020)
Cognition and affect have had stretched history of influencing the buying behaviour of an individual. The change in one of the dimensions leads to some proportionate change in corresponding factor, and a number of research studies have been carried out to ascertain the role of cognition and affect in consumer decision making. But most of the studies lack the evidence of scientific reliability and validity and nature of itemization in previous scales/papers has not been comprehensive as well. In the current endeavour, application of exploratory factor analysis and structure equation modelling has significantly tested the reliability and validity measures needed for impulsive buying scale that would largely facilitate different stake holders. This paper explores the process for how highly reliable and valid indicators of cognition and affect have been developed. The research design employed was a mixture of both exploratory and descriptive approaches that assisted author in classifying factors along with underlying items. Structured questionnaire was employed for the collection of data from the respondents. For validation and development of the modified scale, a set of reliable and scientific tools were employed included. Overall findings revealed that the instrument is vastly consistent and possesses both discriminant and convergent validity. Additionally, other reliability forms are on higher side which sustains the reliability of the scale. The current study will have larger credibility for researchers in the area of organizational behaviour, consumer behaviour and in other interdisciplinary areas.
Keywords: 650; Reliability; Validity; Cognition; Affect; Impulsiveness